Pengaruh Transparansi, Sistem Pengendalian Internal dan Kualitas Sumber Daya Manusia terhadap Akuntabilitas Pengelolaan Keuangan Nagari: Studi Empiris pada Nagari di Kota Pariaman - Ratih Amelia Fitri; Fefri Indra Arza (Universitas Negeri Padang, 2023)
The purpose of this research is to obtain empirical evidence and find out the effect of transparency, internal control system and human resource quality on the responsibility of village financial management. The population of this study is Pariaman town village office up to 110 people who were sampled. The sampling technique uses total sampling. The data source of this study is primary data using questionnaire data collection methods.Data analysis In the method of this study, multiple linear regression analysis is used, where the dependent variable is financial management Accountability and the independent variables are transparency, internal control systems and staff quality.The results of this study show that transparency, internal control systems and staff quality do not affect accountability for village financial management.